THE IMPACT OF FUNCTIONAL INTELLIGENCE IN ENHANCING OUTSTANDING PERFORMANCE-AN ANALYTICAL STUDY IN THE GENERAL DIRECTORATE OF EDUCATION IN SALAH AL-DIN (World Economics and Finance Bulletin, 2025)
Through this research, we seek to demonstrate the impact of functional intelligence on outstanding performance in the General Directorate of Education of Salah al-Din. To answer the goal of the research, the hypothetical research scheme was presented, which reflects the nature of the relationships of correlation and influence between the dimensions of functional intelligence represented by (collecting and analyzing data, functional knowledge, making job decisions, supporting the job position) and between the dimensions of outstanding performance represented by (leadership excellence, service excellence, and cognitive excellence). From that chart emerged a set of main and subsidiary hypotheses that were tested using a set of statistical methods to process the data obtained through The answers of the individuals surveyed in the General Directorate of Salah al-Din Education were the research sample, and the questionnaire form was adopted as the main tool in the research.